MD simulation of the interaction between sialoglycans and the second sialic acid binding site of influenza A virus N1 neuraminidase. Issue 2 (29th January 2021) - Elli, Stefano; Gambacorta, Nicola; Rudd, Timothy R.; Matrosovich, Mikhail; Guerrini, Marco
Abstract : The neuraminidases (NAs) of avian influenza viruses (IAVs) contain a second sialic acid-binding site (2SBS), historically known as the hemadsorption site, which is separated from the sialyl-hydrolase catalytic site and serves to facilitate NA catalytic activity towards multivalent sialyl-capped glycoconjugates. Transmission and adaptation of avian IAVs to humans decreases hemadsorption and catalytic activities of the NA. Here, we report the molecular recognition features of the NA 2SBS of two pandemic H1N1 IAVs, A/Brevig Mission /1/1918 (BM18) and A/California/04/2009 (CA09), differing by their 2SBS activity. Using explicit solvent MD simulation, molecular mechanics, and glycosidic conformation analysis we initially analyzed the interactions of BM18 2SBS with two sialyllacto-N-tetraose pentasaccharides, 3′SLN-LC and 6′SLN-LC, which are models for the glycan receptors of IAVs in birds and humans, respectively. These studies characterize the binding specificity of BM18 2SBS towards human-type and avian-type receptors and identifies the key amino acids that affects binding. We next compared the interactions of the 2SBSs of BM18 and CA09 with 6′SLN-LC, revealing the critical effect of amino acid 372 on binding. Our results expand the current knowledge of the molecular features of NA 2SBSs and its alteration during the adaptation of avian IAVs to humans.